(untitled) (Al-Qamar, 2021)
While some Sufis follow a literal reading of the Qur’an, others emphasize the emotional and spiritual components and ramifications of Islamic concepts. This paper maintains that the Sufi poets of Persia belong to the second category. The primary mission of their poetry has been to create an emotional connection with God through the process of experiencing Divine, or connecting with God on a personal level. This massage is abundantly expressed in the Sufi poetry through a use of symbolism. This paper highlights the way various symbols are used to express the fundamental ideas of Sufi ideology.